The early reception of Rosa Luxemburg's theory of imperialism. (October 2013) - Gaido, Daniel; Quiroga, Manuel
This article deals with the reception of Rosa Luxemburg's The Accumulation of Capital: A Contribution to the Economic Explanation of Imperialism in the Second International before the start of the First World War. Our analysis shows that, if the condemnation of The Accumulation of Capital by the political right and centre was almost unanimous, its acceptance by the left was far from universal. In fact, both Lenin and Pannekoek rejected Luxemburg's theory, adopting instead the economic analysis of an important spokesman of the centre, the Austro-Marxist Rudolf Hilferding. Our work concludes by analysing the reasons for those theoretical differences.